ANALISA PELAYANAN INTEGRASI MODA (PARK AND RIDE) DENGAN HALTE TRANSJAKARTA KORIDOR 6 (RAGUNAN -KUNINGAN) - Herdiansyah, Januar; Yenita (Globalwriting Academica Consulting & Publishing, 2023)
In analyzing the modal integration service for park and ride facilities at the Transjakarta Route 6 bus stop, this analysis focuses on the effect of the existence of existing park and ride facilities to support the policy of changing the occupancy of private vehicles to switching to Mass Transportation or Bus Rapid Transit. The purpose of this analysis is to find out about the variables related to priority services to be handled with a 5-dimensional analysis of service quality in the form of tangible, assurance, reliability, responsiveness and empathy based on the opinions of Transjakarta passengers on park and ride facilities that have been provided, as well as the resulting impact in terms of daily transportation costs that affect the percentage of monthly transportation expenses.